The impact of strength training on functional capacity and quality of life of sedentary elderly people: A literature review (Research, Society and Development, 2025)
Population aging has increased the prevalence of conditions such as sarcopenia and loss of functional capacity, which compromise the quality of life of sedentary older adults. In this context, strength training has been identified as an effective strategy to mitigate these effects, providing both physical and psychosocial benefits. The aim of this study was to analyze the impact of strength training on functional capacity and quality of life in sedentary older adults through a literature review. The PubMed and Virtual Health Library (BVS) databases were consulted, identifying 12 articles, all of which were included in the final analysis. The results indicated that resistance training promotes gains in muscle strength, reduction of sarcopenia, and improvements in mobility, preventing falls and increasing functional autonomy. In addition, a positive impact was observed on cardiovascular health and quality of life, including a reduction in depressive symptoms. Evidence also suggests that the benefits of exercise may persist partially even after periods of detraining, highlighting the importance of long-term adherence. It is concluded that strength training is a safe, effective, and essential intervention for promoting health and quality of life in sedentary older adults, serving as a relevant basis for exercise prescription in this population.